2015
DOI: 10.1007/s12160-014-9653-4
|View full text |Cite
|
Sign up to set email alerts
|

Expectations Are More Predictive of Behavior than Behavioral Intentions: Evidence from Two Prospective Studies

Abstract: Background. Understanding the gap between people's behavioral intentions and their subsequent behavior is a key problem for behavioral scientists, but little attention has been paid to how behavioral intentions are operationalized.Purpose. Test the distinction between asking people what they intend to do, as opposed to what they expect they will do.Methods. Two prospective studies were conducted in the domains of student alcohol consumption (N = 152) and weight loss among overweight/obese people (N = 141).Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 24 publications
1
50
0
1
Order By: Relevance
“…Results of this study revealed that students developed self‐expectations of better role performance through the great respect they felt toward the silent mentors and their families. Self‐expectation is a predictor of behavior (Armitage et al, ). Students’ high academic expectations stimulate critical thinking and a reflective approach to learning (Rodriguez, ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study revealed that students developed self‐expectations of better role performance through the great respect they felt toward the silent mentors and their families. Self‐expectation is a predictor of behavior (Armitage et al, ). Students’ high academic expectations stimulate critical thinking and a reflective approach to learning (Rodriguez, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Warshaw and Davis () have argued that behavioural expectations tap into perceptions of behavioural inhibitors and facilitators, whereas behavioural intentions do not (e.g., a person people may not intend to exceed the speed limit while driving but still think they are likely to do it because they know they are likely to encounter situations that tempt the behaviour or make it difficult to avoid). Likewise, Armitage, Norman, Alganem, and Conner () have argued that asking people about their behavioural expectations elicits more reflective processing than does asking them about their behavioural intentions. Behavioural expectations and behavioural intentions are also empirically distinct.…”
Section: The Prototype Willingness Modelmentioning
confidence: 99%
“…Likewise, Armitage, Norman, Alganem, and Conner (2015) have argued that asking people about their behavioural expectations elicits more reflective processing than does asking them about their behavioural intentions. Behavioural expectations and behavioural intentions are also empirically distinct.…”
Section: The Prototype Willingness Modelmentioning
confidence: 99%
“…This study suggests that weight loss self‐efficacy is an important predictor for risk perceptions of bariatric surgery outcomes. It is also important to consider if the severity of obesity itself was a factor in participants' calculation of their willingness to take risk . There are also implications for individuals with low weight loss self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to consider if the severity of obesity itself was a factor in participants' calculation of their willingness to take risk. 11,12,29,30 There are also implications for individuals with low weight loss self- should be strategically tested and applied when aiming to increase risk perceptions or intervene with this target population. [32][33][34][35] This study's contribution should be considered within its limitations.…”
Section: Discussionmentioning
confidence: 99%